Spatio-temporal access to protected areas from Australian significant urban areas - Chris Taylor; Maldwyn John Evans; Sarah Rees; David Lindenmayer (Landscape and Urban Planning, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Influence of pillar plants in vegetation patches on soil carbon in hyperarid ecosystems of the AlUla region - Oscar Pascal Malou; Stéphane Boivin; Baptiste Kerfriden; David Sebag; Jérôme Nespoulous; Ines Ben Ammar; Hassan Boukcim; Yassine Fendane; Sami D. Almalki; Shauna K. Rees; Abdalsamad Aldabaa; Ahmed H. Mohamed; et al. (Journal of Arid Environments, 2026)

Building trust in the integration of artificial intelligence into chemical risk assessment: findings from the 2024 ECETOC workshop - Timothy W. Gant; Alistair Boxall; Daniel Burgwinkel; Maryam Zare Jeddi; Ivo Djidrovski; Steffi Friedrichs; Barry Hardy; Thomas Hartung; Daniela Holland; Andreas Karwath; Anne Kienhuis; Nicole Kleinstreuer; et al. (Archives of Toxicology, 2026)
Artificial Intelligence (AI) is increasingly influencing chemical risk assessment, enabling faster, more comprehensive, and potentially more ethical assessments. The application of AI in chemical risk assessment refers to both generative and predictive algorithms encompassing machine learning, to analyse complex chemical, biological, and environmental data and provide insights into adverse effect potential for humans and ecosystems. AI systems support the prediction of chemical hazards, exposure levels, and adverse effects by learning from experimental results, mechanistic models, and regulatory datasets, thereby enhancing the efficiency of safety evaluations. In October 2024, ECETOC held an international workshop, with experts from academia, industry, and regulatory bodies, to reflect upon the historical challenges in integrating multidimensional omics technologies into chemical regulation and explore the current capabilities and future potential of AI in toxicology and regulatory science. Discussions emphasised that implementation of Findable, Accessible, Interoperable, and Reusable (FAIR) data principles is not just a best practice but rather a prerequisite for building transparent, reliable, and unbiased AI systems. The reliability of AI in producing scientifically valid and socially responsible outcomes depends fundamentally on the availability of FAIR data. However, ensuring trustworthiness also requires robust governance frameworks that go beyond data and human oversight. Critical enablers of responsible AI in chemical risk assessment are rigorous governance, explainability, fit-for-purpose applications, and human oversight. ECETOC supports the development of flexible and iterative frameworks advancing development, validation, transparency, accountability, and trust in AI applications in chemicals regulation.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The palaeogeography of the Bass Strait land-bridge, a vital zone of human and biological connectivity across southeastern Australia - David M. Kennedy; Ali Jalali; Bruno David; Matthew C. McDowell; Rachel A. Nanson; Ashleigh J. Rogers; Russell Mullett; Joanna Fresløv; Jessie Birkett-Rees; Juliet Sefton; Daniel Ierodiaconou (Quaternary Science Reviews, 2025)

Patterns and Drivers of Phylogenetic Beta Diversity in the Forests and Savannas of Africa - Mathew Rees; Adeline Fayolle; John L. Godlee; Anais P. Gorel; David J. Harris; Kyle G. Dexter (Journal of Biogeography, 2025)
Aim Studying beta diversity, or the variation in species composition among communities, can give insights into plant community assembly over space and time. If different biomes show contrasting large‐scale beta‐diversity patterns, this can indicate divergent evolutionary histories or ecological processes that then drive species turnover among communities. Here, we examine phylogenetic beta‐diversity patterns across Africa in forest and savanna assemblages, the two most widespread tropical biomes on the continent. We hypothesise that savannas will show lower phylogenetic beta diversity due to their younger evolutionary history. Location Tropical Africa. Taxon Woody angiosperms. Methods We gathered 301,159 occurrences of woody angiosperms representing 1883 forest species and 1302 savanna species. We compared levels of phylogenetic beta diversity between forest and savanna assemblages, analysed spatial patterns of phylogenetic beta diversity using 1° grid cells and modelled their relationship with climate, disturbance and geographical distance. Results We found that savannas show greater relative regional phylogenetic beta diversity, whereas forest assemblages show greater relative local phylogenetic beta diversity. The spatial distribution of beta diversity showed strong East–West patterns for both forests and savannas, aligned with a major floristic discontinuity associated with the Albertine rift. Our results also highlighted West Africa as showing a high amount of compositional change for both biomes, arranged along an aridity gradient. Variance partitioning showed that predictors linked to precipitation were the main drivers of compositional change for both forests and savannas, but the importance of individual predictors was different in each biome. Main Conclusions Contrary to our expectations, our results indicate that savannas may have a deeper and richer evolutionary history than suggested by previous studies and that individual regions of both forest and savanna have high conservation value. Finally, our results demonstrate that environmental filtering is the dominant force influencing the assembly of these two important biomes at a continental spatial scale.

Quantifying the effects of extreme flooding on coastal reef fishes - Matthew J. Rees; Nathan A. Knott; David Harasti; Timothy C. Ingleton; Hamish A. Malcolm; Rachel Przeslawski (Ecology, 2025)
The ecological impacts of extreme floods to benthic ecosystems in oceanic environments remain unclear, as events are difficult to observe and quantify. Between 2020 and 2022, an unusually long La Niña resulted in substantial flooding across southeastern Australia. Major floods in the Hawkesbury‐Nepean River led to an unprecedented flood plume extending ~70 km offshore to depths of ~50 m, exposing coastal biodiversity to rare environmental conditions. Here, we use long‐term monitoring data to quantify the impacts of large‐scale flooding to coastal rocky reef fishes. Flooding reduced the total abundance and species richness of reef fishes by 50% and 13%, respectively. Declines were primarily due to reductions in the abundance of planktivores (−75%) and benthic invertivores (−40%). Assemblages at reference locations isolated from large rivers were stable across the study period, indicating observed patterns were in response to floods. Surveys 1‐year post flooding signaled that benthic invertivores were beginning to recover but not planktivores. Our results demonstrate the detrimental impacts of extreme flooding to some coastal rocky reef fishes. Given projected increases in the severity and frequency of rainfall due to climate change, our findings suggest that extreme flooding may compromise ecosystem functions and services provided by rocky reef fish in a future climate.

The CURTAIN feasibility study: Exploring a food-themed reminiscence theatre intervention to improve the nutrition of older adults living in residential care homes - Chris J. McLeod; David W. Maidment; Catherine Rees (Appetite, 2025)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Pathways to global coordination in space weather: International organizations, initiatives, and space agencies - Mamoru Ishii; Joaquim Eduardo Rezende Costa; Maria M. Kuznetsova; Jesse Andries; Natchimuthuk Gopalswamy; Anna Belehaki; Lucilla Alfonsi; Kazuo Shiokawa; Iwona Stanislawska; Suzy Bingham; Vladimir Kalegaev; W. Kent Tobiska; et al. (Advances in Space Research, 2024)

Net Zero requires ambitious greenhouse gas emission reductions on beef and sheep farms coordinated with afforestation and other land use change measures - Louise C. McNicol; Non G. Williams; Dave Chadwick; David Styles; Robert M. Rees; Rachael Ramsey; A. Prysor Williams (Agricultural Systems, 2024)

An evidence base of ecosystems services provided by diadromous fish in the European Atlantic Area - Matthew Ashley; Arantza Murillas; Angela Muench; Cristina Marta-Pedroso; Lynda Rodwell; Sian Rees; Emma Rendle; Tea Bašić; Gordon H. Copp; Estibaliz Díaz; David J. Nachón; Patrick Lambert; et al. (Ecosystem Services, 2023)

Nature-based solutions for leveed river corridors - Matthew L. Chambers; Charles B. van Rees; Brian P. Bledsoe; David Crane; Susana Ferreira; Damon M. Hall; Rod W. Lammers; Craig E. Landry; Donald R. Nelson; Matt Shudtz; Burton C. Suedel (Anthropocene, 2023)

Environmental and land use consequences of replacing milk and beef with plant-based alternatives - Marcela Porto Costa; Sophie Saget; Beate Zimmermann; Eckart Petig; Elisabeth Angenendt; Robert M. Rees; David Chadwick; James Gibbons; Shailesh Shrestha; Michael Williams; David Styles (Journal of Cleaner Production, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

A decade of nature: Evolving approaches to Melbourne’s ‘nature in the city’ - Judy Bush; Cathy Oke; Ariana Dickey; Jacinta Humphrey; Lee Harrison; Marco Amati; Giorgia Fornari; Kylie Soanes; David Callow; Rodney Van der Ree (Landscape and Urban Planning, 2023)

First recorded occurrence of the parasitic barnacle ( Anelasma squalicola ) on a Greenland shark ( Somniosus microcephalus ) in the Canadian Arctic - Eric Ste‐Marie; Henrik Glenner; David J. Rees; Nigel E. Hussey (Journal of Fish Biology, 2023)
A solitary Anelasma squalicola specimen was collected from the cloaca of a Greenland shark ( Somniosus microcephalus ), the first time this association has been recorded. The specimen's identity was confirmed through morphological and genetic assessment (mitochondrial markers: COI and control region). A. squalicola is a species typically associated with deep‐sea lantern sharks (Etmopteridae) and, until the present observation, had never been observed at a sexually mature size in the absence of a mating partner. Given the reported negative effects of this parasite on its hosts, monitoring Greenland sharks for additional cases is recommended.

Co-pyrolysis of biosolids with lignocellulosic biomass: Effect of feedstock on product yield and composition - Nimesha Rathnayake; Savankumar Patel; Ibrahim Gbolahan Hakeem; Jorge Pazferreiro; Abhishek Sharma; Rajender Gupta; Catherine Rees; David Bergmann; Judy Blackbeard; Aravind Surapaneni; Kalpit Shah (Process Safety and Environmental Protection, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Accelerating the development of biological nitrification inhibition as a viable nitrous oxide mitigation strategy in grazed livestock systems - Cecile A. M. de Klein; Saman Bowatte; Priscila L. Simon; Jacobo Arango; Laura M. Cardenas; David R. Chadwick; Jeroen Pijlman; Robert M. Rees; Karl G. Richards; Guntur V. Subbarao; David Whitehead (Biology and Fertility of Soils, 2022)
This position paper summarizes the current understanding of biological nitrification inhibition (BNI) to identify research needs for accelerating the development of BNI as a N 2 O mitigation strategy for grazed livestock systems. We propose that the initial research focus should be on the systematic screening of agronomically desirable plants for their BNI potency and N 2 O reduction potential. This requires the development of in situ screening methods that can be combined with reliable N 2 O emission measurements and microbial and metabolomic analyses to confirm the selective inhibition of nitrification. As BNI-induced reductions in N 2 O emissions can occur by directly inhibiting nitrification, or via indirect effects on other N transformations, it is also important to measure gross N transformation rates to disentangle these direct and indirect effects. However, an equally important challenge will be to discern the apparent influence of soil N fertility status on the release of BNIs, particularly for more intensively managed grazing systems.

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The second rhizocephalan species, Lernaeodiscus kasyanovi sp. nov. (Cirripedia: Rhizocephala: Peltogastridae), parasitizing the porcellanid crab Pachycheles stevensii Stimpson, 1858 (Decapoda: Anomura: Porcellanidae), from Russian waters of the Sea of Japan - Olga M. Korn; Darya D. Golubinskaya; David J. Rees; Henrik Glenner; Jens T. Høeg (Marine Biodiversity, 2021)

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Diversity, Distribution and Phylogenetic Relationships of Deep-Sea Lithistids (Porifera, Heteroscleromorpha) of the Azores Archipelago - Joana R. Xavier; David J. Rees; Raquel Pereira; Ana Colaço; Christopher K. Pham; Francisca C. Carvalho (Frontiers in Marine Science, 2021)
Lithistid sponges are globally distributed in temperate and sub-tropical areas, constituting an important component of deep-sea benthic communities where they form structurally complex and vulnerable marine ecosystems (VMEs). In this study, we assess the diversity and investigate the spatial and bathymetric distribution of the lithistid sponges of the Azores archipelago (North Atlantic) based on historical records and examination of samples accidentally collected during deep-sea longline fishing operations in the region. Eleven lithistid species are recognized to occur in the Azores, including Leiodermatium tuba , recently described from material collected in several Northeast Atlantic seamounts that is hereby reported for the first time to the archipelago. We provide molecular barcodes (mtDNA COI and rRNA 28S) for seven of these species, including Discodermia ramifera , Macandrewia azorica , and Exsuperantia archipelagus , for which the Azores constitutes the type locality. We further discuss the phylogenetic and biogeographic affinities of the Azorean lithistids in the context of the Porifera classification, and the wider Northeast Atlantic upper bathyal fauna. Our study also warrants the addition of some lithistid species to the list of VME indicators for the Northeast Atlantic in support of the sustainable management and conservation of these species and habitats, as well as the ecological functions they deliver.

Can N 2 O emissions offset the benefits from soil organic carbon storage? - Bertrand Guenet; Benoit Gabrielle; Claire Chenu; Dominique Arrouays; Jérôme Balesdent; Martial Bernoux; Elisa Bruni; Jean‐Pierre Caliman; Rémi Cardinael; Songchao Chen; Philippe Ciais; Dominique Desbois; et al. (Global Change Biology, 2021)
To respect the Paris agreement targeting a limitation of global warming below 2°C by 2100, and possibly below 1.5°C, drastic reductions of greenhouse gas emissions are mandatory but not sufficient. Large‐scale deployment of other climate mitigation strategies is also necessary. Among these, increasing soil organic carbon (SOC) stocks is an important lever because carbon in soils can be stored for long periods and land management options to achieve this already exist and have been widely tested. However, agricultural soils are also an important source of nitrous oxide (N 2 O), a powerful greenhouse gas, and increasing SOC may influence N 2 O emissions, likely causing an increase in many cases, thus tending to offset the climate change benefit from increased SOC storage. Here we review the main agricultural management options for increasing SOC stocks. We evaluate the amount of SOC that can be stored as well as resulting changes in N 2 O emissions to better estimate the climate benefits of these management options. Based on quantitative data obtained from published meta‐analyses and from our current level of understanding, we conclude that the climate mitigation induced by increased SOC storage is generally overestimated if associated N 2 O emissions are not considered but, with the exception of reduced tillage, is never fully offset. Some options (e.g. biochar or non‐pyrogenic C amendment application) may even decrease N 2 O emissions.

Representing crop rotations in life cycle assessment: a review of legume LCA studies - Marcela Porto Costa; David Chadwick; Sophie Saget; Robert M. Rees; Michael Williams; David Styles (The International Journal of Life Cycle Assessment, 2020)
Purpose There is an imperative to accurately assess the environmental sustainability of crop system interventions in the context of food security and climate change. Previous studies have indicated that the incorporation of legumes into cereal rotations could reduce overall environmental burdens from cropping systems. However, most life cycle assessment (LCA) studies focus on individual crops and miss environmental consequences of inter-annual crop sequence and nutrient cycling effects. This review investigates state-of-the-art representation of inter-crop rotation effects within legume LCA studies. Methods A literature review was undertaken, starting with a search for all peer-reviewed articles with combinations of ‘LCA’, ‘legumes’ and ‘rotations’ or synonyms thereof. In total, 3180 articles were obtained. Articles were screened for compliance with all of the following requirements: (i) reporting results based on LCA or life cycle inventory methodology; (ii) inclusion of (a) legume(s); (iii) the legume(s) is/are analysed within the context of a wider cropping system (i.e. rotation or intercropping). Seventy articles satisfying these requirements were analysed. Results and discussion We identified three broad approaches to legume LCA. Most studies involved simple attributional LCA disregarding important interactions across years and crops in rotations. N-fertilizer reduction through legume residue N carryover is either disregarded or the benefit is attributed to the following crop in such studies, whilst N leaching burdens from residues are usually attributed to the legume crop. Some studies applied robust allocation approaches and/or complex functional units to enable analysis of entire rotation sequences, accounting for nutrient cycling and break crop effects. Finally, a few studies applied consequential LCA to identify downstream substitution effects, though these studies did not simultaneously account for agronomic effects of rotational sequence changes. Conclusions We recommend that LCA studies for legume cropping systems should (i) evaluate entire rotations; (ii) represent nitrogen and ideally carbon cycling; (iii) for attributional studies, define at least two functional units, where one should encompass the multifunctional outputs of an entire rotation and the other should enable product footprints to be calculated; (iv) for CLCA studies, account for both agronomic changes in rotations and markets effects; (v) include impact categories that reflect hotspots for agricultural production.

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Nutrient and microbial water quality of the upper Ganga River, India: identification of pollution sources - Michael J. Bowes; Daniel S. Read; Himanshu Joshi; Rajiv Sinha; Aqib Ansari; Moushumi Hazra; Monica Simon; Rajesh Vishwakarma; Linda K. Armstrong; David J. E. Nicholls; Heather D. Wickham; Jade Ward; et al. (Environmental Monitoring and Assessment, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Is subarctic forest advance able to keep pace with climate change? - W. Gareth Rees; Annika Hofgaard; Stéphane Boudreau; David M. Cairns; Karen Harper; Steven Mamet; Ingrid Mathisen; Zuzanna Swirad; Olga Tutubalina (Global Change Biology, 2020)
Recent climate warming and scenarios for further warming have led to expectations of rapid movement of ecological boundaries. Here we focus on the circumarctic forest–tundra ecotone (FTE), which represents an important bioclimatic zone with feedbacks from forest advance and corresponding tundra disappearance (up to 50% loss predicted this century) driving widespread ecological and climatic changes. We address FTE advance and climate history relations over the 20th century, using FTE response data from 151 sites across the circumarctic area and site‐specific climate data. Specifically, we investigate spatial uniformity of FTE advance, statistical associations with 20th century climate trends, and whether advance rates match climate change velocities (CCVs). Study sites diverged into four regions (Eastern Canada; Central and Western Canada and Alaska; Siberia; and Western Eurasia) based on their climate history, although all were characterized by similar qualitative patterns of behaviour (with about half of the sites showing advancing behaviour). The main associations between climate trend variables and behaviour indicate the importance of precipitation rather than temperature for both qualitative and quantitative behaviours, and the importance of non‐growing season as well as growing season months. Poleward latitudinal advance rates differed significantly among regions, being smallest in Eastern Canada (~10 m/year) and largest in Western Eurasia (~100 m/year). These rates were 1–2 orders of magnitude smaller than expected if vegetation distribution remained in equilibrium with climate. The many biotic and abiotic factors influencing FTE behaviour make poleward advance rates matching predicted 21st century CCVs (~10 3 –10 4 m/year) unlikely. The lack of empirical evidence for swift forest relocation and the discrepancy between CCV and FTE response contradict equilibrium model‐based assumptions and warrant caution when assessing global‐change‐related biotic and abiotic implications, including land–atmosphere feedbacks and carbon sequestration.

Characterising the biophysical, economic and social impacts of soil carbon sequestration as a greenhouse gas removal technology - Alasdair J. Sykes; Michael Macleod; Vera Eory; Robert M. Rees; Florian Payen; Vasilis Myrgiotis; Mathew Williams; Saran Sohi; Jon Hillier; Dominic Moran; David A. C. Manning; Pietro Goglio; et al. (Global Change Biology, 2020)
To limit warming to well below 2°C, most scenario projections rely on greenhouse gas removal technologies (GGRTs); one such GGRT uses soil carbon sequestration (SCS) in agricultural land. In addition to their role in mitigating climate change, SCS practices play a role in delivering agroecosystem resilience, climate change adaptability and food security. Environmental heterogeneity and differences in agricultural practices challenge the practical implementation of SCS, and our analysis addresses the associated knowledge gap. Previous assessments have focused on global potentials, but there is a need among policymakers to operationalise SCS. Here, we assess a range of practices already proposed to deliver SCS, and distil these into a subset of specific measures. We provide a multidisciplinary summary of the barriers and potential incentives towards practical implementation of these measures. First, we identify specific practices with potential for both a positive impact on SCS at farm level and an uptake rate compatible with global impact. These focus on: (a) optimising crop primary productivity (e.g. nutrient optimisation, pH management, irrigation); (b) reducing soil disturbance and managing soil physical properties (e.g. improved rotations, minimum till); (c) minimising deliberate removal of C or lateral transport via erosion processes (e.g. support measures, bare fallow reduction); (d) addition of C produced outside the system (e.g. organic manure amendments, biochar addition); (e) provision of additional C inputs within the cropping system (e.g. agroforestry, cover cropping). We then consider economic and non‐cost barriers and incentives for land managers implementing these measures, along with the potential externalised impacts of implementation. This offers a framework and reference point for holistic assessment of the impacts of SCS. Finally, we summarise and discuss the ability of extant scientific approaches to quantify the technical potential and externalities of SCS measures, and the barriers and incentives to their implementation in global agricultural systems.

The FluxEngine air–sea gas flux toolbox: simplified interface and extensions for in situ analyses and multiple sparingly soluble gases - Thomas Holding; Ian G. Ashton; Jamie D. Shutler; Peter E. Land; Philip D. Nightingale; Andrew P. Rees; Ian Brown; Jean-Francois Piolle; Annette Kock; Hermann W. Bange; David K. Woolf; Lonneke Goddijn-Murphy; et al. (Ocean Science, 2019)
The flow (flux) of climate-critical gases, such as carbon dioxide (CO2), between the ocean and the atmosphere is a fundamental component of our climate and an important driver of the biogeochemical systems within the oceans. Therefore, the accurate calculation of these air–sea gas fluxes is critical if we are to monitor the oceans and assess the impact that these gases are having on Earth's climate and ecosystems. FluxEngine is an open-source software toolbox that allows users to easily perform calculations of air–sea gas fluxes from model, in situ, and Earth observation data. The original development and verification of the toolbox was described in a previous publication. The toolbox has now been considerably updated to allow for its use as a Python library, to enable simplified installation, to ensure verification of its installation, to enable the handling of multiple sparingly soluble gases, and to enable the greatly expanded functionality for supporting in situ dataset analyses. This new functionality for supporting in situ analyses includes user-defined grids, time periods and projections, the ability to reanalyse in situ CO2 data to a common temperature dataset, and the ability to easily calculate gas fluxes using in situ data from drifting buoys, fixed moorings, and research cruises. Here we describe these new capabilities and demonstrate their application through illustrative case studies. The first case study demonstrates the workflow for accurately calculating CO2 fluxes using in situ data from four research cruises from the Surface Ocean CO2 ATlas (SOCAT) database. The second case study calculates air–sea CO2 fluxes using in situ data from a fixed monitoring station in the Baltic Sea. The third case study focuses on nitrous oxide (N2O) and, through a user-defined gas transfer parameterisation, identifies that biological surfactants in the North Atlantic could suppress individual N2O sea–air gas fluxes by up to 13 %. The fourth and final case study illustrates how a dissipation-based gas transfer parameterisation can be implemented and used. The updated version of the toolbox (version 3) and all documentation is now freely available.

The role of WNK in modulation of KCl cotransport activity in red cells from normal individuals and patients with sickle cell anaemia - David C.-Y. Lu; Anke Hannemann; Rasiqh Wadud; David C. Rees; John N. Brewin; Philip S. Low; John S. Gibson (Pflügers Archiv - European Journal of Physiology, 2019)
Abnormal activity of red cell KCl cotransport (KCC) is involved in pathogenesis of sickle cell anaemia (SCA). KCC-mediated solute loss causes shrinkage, concentrates HbS, and promotes HbS polymerisation. Red cell KCC also responds to various stimuli including pH, volume, urea, and oxygen tension, and regulation involves protein phosphorylation. The main aim of this study was to investigate the role of the WNK/SPAK/OSR1 pathway in sickle cells. The pan WNK inhibitor WNK463 stimulated KCC with an EC 50 of 10.9 ± 1.1 nM and 7.9 ± 1.2 nM in sickle and normal red cells, respectively. SPAK/OSR1 inhibitors had little effect. The action of WNK463 was not additive with other kinase inhibitors (staurosporine and N -ethylmaleimide). Its effects were largely abrogated by pre-treatment with the phosphatase inhibitor calyculin A. WNK463 also reduced the effects of physiological KCC stimuli (pH, volume, urea) and abolished any response of KCC to changes in oxygen tension. Finally, although protein kinases have been implicated in regulation of phosphatidylserine exposure, WNK463 had no effect. Findings indicate a predominant role for WNKs in control of KCC in sickle cells but an apparent absence of downstream involvement of SPAK/OSR1. A more complete understanding of the mechanisms will inform pathogenesis whilst manipulation of WNK activity represents a potential therapeutic approach.

Characterization and detection of maize-associated pteridovirus (MaPV), infecting maize (Zea mays) in the Arusha region of Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest Mbega (European Journal of Plant Pathology, 2019)

Diversity and distribution of Maize-associated totivirus strains from Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Virus Genes, 2019)

Molecular characterization of Morogoro maize-associated virus, a nucleorhabdovirus detected in maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Archives of Virology, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Large-scale managed retreat and structural protection following the 2011 Japan tsunami - Nicholas Pinter; Mikio Ishiwateri; Atsuko Nonoguchi; Yumiko Tanaka; David Casagrande; Susan Durden; James Rees (Natural Hazards, 2019)

First report of maize yellow mosaic virus (MaYMV) on maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherstone; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingston Mashingaidze; Dave Kenneth Berger; Tanya Welgemoed; Gerhard Pietersen; Susanna Elizabeth Schulze; Barnabas Kiula; et al. (Journal of Plant Pathology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Chinese cropping systems are a net source of greenhouse gases despite soil carbon sequestration - Bing Gao; Tao Huang; Xiaotang Ju; Baojing Gu; Wei Huang; Lilai Xu; Robert M. Rees; David S. Powlson; Pete Smith; Shenghui Cui (Global Change Biology, 2018)
Soil carbon sequestration is being considered as a potential pathway to mitigate climate change. Cropland soils could provide a sink for carbon that can be modified by farming practices; however, they can also act as a source of greenhouse gases ( GHG ), including not only nitrous oxide (N 2 O) and methane ( CH 4 ), but also the upstream carbon dioxide ( CO 2 ) emissions associated with agronomic management. These latter emissions are also sometimes termed “hidden” or “embedded” CO 2 . In this paper, we estimated the net GHG balance for Chinese cropping systems by considering the balance of soil carbon sequestration, N 2 O and CH 4 emissions, and the upstream CO 2 emissions of agronomic management from a life cycle perspective during 2000–2017. Results showed that although soil organic carbon ( SOC ) increased by 23.2 ± 8.6 Tg C per year, the soil N 2 O and CH 4 emissions plus upstream CO 2 emissions arising from agronomic management added 269.5 ± 21.1 Tg C‐eq per year to the atmosphere. These findings demonstrate that Chinese cropping systems are a net source of GHG emissions and that total GHG emissions are about 12 times larger than carbon uptake by soil sequestration. There were large variations between different cropping systems in the net GHG balance ranging from 328 to 7,567 kg C‐eq ha −1 year −1 , but all systems act as a net GHG source to the atmosphere. The main sources of total GHG emissions are nitrogen fertilization (emissions during production and application), power use for irrigation, and soil N 2 O and CH 4 emissions. Optimizing agronomic management practices, especially fertilization, irrigation, plastic mulching, and crop residues to reduce total GHG emissions from the whole chain is urgently required in order to develop a low‐carbon future for Chinese crop production.

Application of Chloroplast Phylogenomics to Resolve Species Relationships Within the Plant Genus Amaranthus - Erika Viljoen; Damaris A. Odeny; Martin P. A. Coetzee; Dave K. Berger; David J. G. Rees (Journal of Molecular Evolution, 2018)

Global biogeography of mating system variation in seed plants - David A. Moeller; Ryan D. Briscoe Runquist; Annika M. Moe; Monica A. Geber; Carol Goodwillie; Pierre‐Olivier Cheptou; Christopher G. Eckert; Elizabeth Elle; Mark O. Johnston; Susan Kalisz; Richard H. Ree; Risa D. Sargent; et al. (Ecology Letters, 2017)
Latitudinal gradients in biotic interactions have been suggested as causes of global patterns of biodiversity and phenotypic variation. Plant biologists have long speculated that outcrossing mating systems are more common at low than high latitudes owing to a greater predictability of plant–pollinator interactions in the tropics; however, these ideas have not previously been tested. Here, we present the first global biogeographic analysis of plant mating systems based on 624 published studies from 492 taxa. We found a weak decline in outcrossing rate towards higher latitudes and among some biomes, but no biogeographic patterns in the frequency of self‐incompatibility. Incorporating life history and growth form into biogeographic analyses reduced or eliminated the importance of latitude and biome in predicting outcrossing or self‐incompatibility. Our results suggest that biogeographic patterns in mating system are more likely a reflection of the frequency of life forms across latitudes rather than the strength of plant–pollinator interactions.

Participant understanding and recall of informed consent for induced pluripotent stem cell biobanking - Tristan McCaughey; Christine Y. Chen; Elisabeth De Smit; Gwyneth Rees; Eva Fenwick; Lisa S. Kearns; David A. Mackey; Casimir MacGregor; Megan Munsie; Anthony L. Cook; Alice Pébay; Alex W. Hewitt (Cell and Tissue Banking, 2016)

The effects of asymmetric competition on the life history of Trinidadian guppies - Ronald D. Bassar; Dylan Z. Childs; Mark Rees; Shripad Tuljapurkar; David N. Reznick; Tim Coulson (Ecology Letters, 2016)
The effects of asymmetric interactions on population dynamics has been widely investigated, but there has been little work aimed at understanding how life history parameters like generation time, life expectancy and the variance in lifetime reproductive success are impacted by different types of competition. We develop a new framework for incorporating trait‐mediated density‐dependence into size‐structured models and use Trinidadian guppies to show how different types of competitive interactions impact life history parameters. Our results show the degree of symmetry in competitive interactions can have dramatic effects on the speed of the life history. For some vital rates, shifting the competitive superiority from small to large individuals resulted in a doubling of the generation time. Such large influences of competitive symmetry on the timescale of demographic processes, and hence evolution, highlights the interwoven nature of ecological and evolutionary processes and the importance of density‐dependence in understanding eco‐evolutionary dynamics.

Spatial distribution of proteins in the quagga mussel adhesive apparatus - David J. Rees; Arash Hanifi; Joseph Manion; Arpita Gantayet; Eli D. Sone (Biofouling, 2016)

Novel Proteins Identified in the Insoluble Byssal Matrix of the Freshwater Zebra Mussel - Arpita Gantayet; David J. Rees; Eli D. Sone (Marine Biotechnology, 2014)

Extensional deformation along the southern boundary of the Gyeonggi Massif, South Korea: structural characteristics, age constraints, and tectonic implications - Raehee Han; Kyoungwon Min; Jin-Han Ree; David A. Foster (International Journal of Earth Sciences, 2014)

Global analysis of satellite tracking data shows that adult green turtles are significantly aggregated in Marine Protected Areas - Rebecca Scott; David J. Hodgson; Matthew J. Witt; Michael S. Coyne; Windia Adnyana; Janice M. Blumenthal; Annette C. Broderick; Ali Fuat Canbolat; Paulo Catry; Stephane Ciccione; Eric Delcroix; Creusa Hitipeuw; et al. (Global Ecology and Biogeography, 2012)
Aim Tracking technologies are often proposed as a method to elucidate the complex migratory life histories of migratory marine vertebrates, allowing spatially explicit threats to be identified and mitigated. We conducted a global analysis of foraging areas of adult green turtles ( Chelonia mydas ) subject to satellite tracking ( n = 145) and the conservation designation of these areas according to International Union for Conservation of Nature criteria. Location The green turtle has a largely circumtropical distribution, with adults migrating up to thousands of kilometres between nesting beaches and foraging areas, typically in neritic seagrass or algal beds. Methods We undertook an assessment of satellite tracking projects that followed the movements of green turtles in tropical and subtropical habitats. This approach was facilitated by the use of the Satellite Tracking and Analysis Tool ( http://www.seaturtle.org ) and the integration of publicly available data on Marine Protected Areas (MPAs). Results We show that turtles aggregate in designated MPAs far more than would be expected by chance when considered globally (35% of all turtles were located within MPAs) or separately by ocean basin (Atlantic 67%, Indian 34%, Mediterranean 19%, Pacific 16%). Furthermore, we show that the size, level of protection and time of establishment of MPAs affects the likelihood of MPAs containing foraging turtles, highlighting the importance of large, well‐established reserves. Main conclusions Our findings constitute compelling evidence of the world‐wide effectiveness of extant MPAs in circumscribing important foraging habitats for a marine megavertebrate.

Inheritance of Flowering Time in Apricot (Prunus armeniaca L.) and Analysis of Linked Quantitative Trait Loci (QTLs) using Simple Sequence Repeat (SSR) Markers - José Antonio Campoy; David Ruiz; José Egea; David Jasper G. Rees; Jean Marc Celton; Pedro Martínez-Gómez (Plant Molecular Biology Reporter, 2011)

Developing Microsatellite Multiplex and Megaplex PCR Systems for High-Throughput Characterization of Breeding Progenies and Linkage Maps Spanning the Apricot (Prunus armeciaca L.) Genome - José Antonio Campoy; Pedro Martínez-Gómez; David Ruiz; Jasper Rees; Jean Marc Celton (Plant Molecular Biology Reporter, 2010)

Identification of a major QTL for time of initial vegetative budbreak in apple (Malus x domestica Borkh.) - Maria M. van Dyk; Mogamat Khashief Soeker; Iwan F. Labuschagne; David Jasper G. Rees (Tree Genetics & Genomes, 2010)

Are We Consuming Too Much—for What? - HERMAN E. DALY; BRIAN CZECH; DAVID L. TRAUGER; WILLIAM E. REES; MANSI GROVER; TRACY DOBSON; STEPHEN C. TROMBULAK (Conservation Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Occupational exposure to ethylene oxide during pregnancy and association with adverse reproductive outcomes - Daniela F. Gresie-Brusin; Danuta Kielkowski; Abednego Baker; Kalavati Channa; David Rees (International Archives of Occupational and Environmental Health, 2007)

Effects of acute fatigue on the volitional and magnetically-evoked electromechanical delay of the knee flexors in males and females - Claire Minshull; Nigel Gleeson; Michelle Walters-Edwards; Roger Eston; David Rees (European Journal of Applied Physiology, 2007)

Are they still viable? Physical conditions and abundance of Daphnia pulicaria resting eggs in sediment cores from lakes in the Tatra Mountains - Silvia Marková; Martin Černý; David J. Rees; Evžen Stuchlík (Biologia, 2006)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Spatial pattern in the precipitation regime of Nepal - Sunil R. Kansakar; David M. Hannah; John Gerrard; Gwyn Rees (International Journal of Climatology, 2004)
A large‐scale perspective is provided upon the nature of precipitation regimes across Nepal by classifying long‐term mean monthly precipitation data for 222 stations. The classification methodology is shown to be a useful tool for identifying underlying spatial structure in precipitation regime shape (seasonal variability) and magnitude (size) in an extreme physical environment where climatological patterns are complex and poorly known. Four precipitation regime shape classes are identified: (a) July–August peaks are typical of western regions; (b) marked July peaks are characteristic of the central region and eastern lowlands; (c) July peaks with gradual onset are mainly concentrated in eastern Middle Mountains; and (d) July–August peaks with winter precipitation are confined to western higher mountains, particularly the Trans‐Himalayan region. Four precipitation regime magnitude classes are found: (a) low regimes clearly dominate western high‐mountain areas but occur more widely across the High Mountains and High Himalaya; (b) intermediate regimes are distributed from east to west at low altitude, dominating the western Terai/Siwaliks; (c) moderately high regimes are widespread but most evident in the Terai (plains) to Middle Mountains of central and eastern parts and eastern high mountains; and (d) high precipitation zones are situated near Pokhara and northeast of the Kathmandu Valley around Langtang. A composite (shape and magnitude) regime classification indicates the key controls upon spatial patterns in Nepalese precipitation to be: length and timing of the summer monsoon (duration decreases east to west with later onset and earlier withdrawal in the west); successively higher altitude, east–west‐trending mountain ranges causing rainfall to decline broadly south–north; topographic barriers that induce local rain shadows (lee) and precipitation hotspots (windward side); and westerly weather systems supplying winter precipitation to the northwest mountains. Although general patterns relating to zonal movement of the summer monsoon and physiographic (mountain ranges) controls upon precipitation may be identified, the role of mountainous relief in yielding localized precipitation patterns is significant. Copyright © 2004 Royal Meteorological Society

On the mechanisms of coexistence among annual-plant species, using neighbourhood techniques and simulation models - David A. Coomes; Mark Rees; Lindsay Turnbull; Sophia Ratcliffe (Plant Ecology, 2002)

Genetic basis of inosine triphosphate pyrophosphohydrolase deficiency - Satoshi Sumi; Anthony Marinaki; Monica Arenas; Lynette Fairbanks; Monsor Shobowale-Bakre; David Rees; Swee Thein; Azhar Ansari; Jeremy Sanderson; Ronney De Abreu; Anne Simmonds; John Duley (Human Genetics, 2002)

High-resolution structures of the oxidized and reduced states of cytochrome c554 from Nitrosomonas europaea - Tina M. Iverson; David M. Arciero; Alan B. Hooper; Douglas C. Rees (JBIC Journal of Biological Inorganic Chemistry, 2001)